Fogyatékos személyek teljesítményértékelésének gyakorlata - Juhász, Csilla (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
Performance management is one of the most important fields of management. For the evaluation of it, I have worked out a questionnary. With the help of the questionnaire I intended to ask about the importance and method of performance evaluation. Based on my examinations I found, that in managers opinions the best way to appraisal disabled person was the individual appraisial. This result is not a suprise, because of disabled persons. Because of the managers' practise there was a difference in opinions. But in theirs opinion the most important possibility was the individual appraisal too. It is nonsense to expect self appraisal from a mentally handicapped person. Examinations show that organizations mainly apply traditional systems and think by the traditional aspect.